Idiopathic giant adrenal calcification: a rare case report - Ji, Zhiqiang; Song, Dalong; Zuo, Hua; Chen, Xiaolong; Ji, Wei; Yang, Jiajun; Wang, Qing; Jiang, Kehua (Frontiers in Oncology, 2024)
Background: We describe a rare case of giant adrenal calcification as the main cause of sudden onset epigastric pain in a 57-year-old female patient. Case description: Computed tomography (CT) of the whole abdomen in this patient showed calcified foci measuring approximately 7.8 × 5.4 × 7.1 cm in the hepatorenal recess, and no enhancement effect was seen. Secondary causes of adrenal calcification in this patient were ruled out, and a rare diagnosis of a primary giant adrenal calcification was made. Subsequently, the right adrenal gland and calcified mass were completely resected. The calcification did not recur during 6 months of follow up. Conclusions: Although other cases of adrenal calcification of unknown origin have been reported, cases of giant idiopathic adrenal calcification are rare. In this case, huge calcification of the right adrenal gland caused abdominal pain, which disappeared after the mass was excised. The etiology, pathogenesis, clinical symptoms, and prognosis of idiopathic adrenal calcification are still unclear. Additional case reports are needed to gain a better understanding of the diagnosis and treatment of this condition.